Estimation of Returns to Scale and the Elasticity of Substitution - Maddala, G. S.; Kadane, J. B. (Econometrica, 1967)
This paper concerns itself with the following problem: Suppose the true production function is of the CES type with constant returns to scale. If we fit an unrestricted Cobb-Douglas production function instead, what is the nature of the bias in the estimate of the returns to scale parameter?